Penerapan Pembelajaran dengan E-Modul Berbasis Kvisoft Flipbook Maker untuk Mata Kualiah Program Linier - Soffi Widyanesti Priwantoro; Burhan Arif; Syariful Fahmi (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2020)
This study aims to improve the independence of students in learning Linear Program by using e-module learning media linear program based on Kvisoft Flipbook Maker. This research is a Classroom Action Research (CAR). This research was conducted in the mathematics education study program FKIP UAD. The results of this study indicate an increase in student learning independence, this is evidenced by the results of interviews with students who showed positive responses. In addition from the observations also obtained a positive response that is the first cycle the average score of learning independence of 52.52% in the second cycle increased by 62.21% and in the third cycle of 72.21%. As well as an increase in completeness of learning outcomes in the first cycle by 50%, then the second cycle increased by 61.53% and in the third cycle of 76.9%.